Method of chemically strengthening a glass-based article
Patent Information
- Application Number
- CN202510565002.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
Smart Images

Figure CN123003159A_ABST
Abstract
Description
Technical Field
[0001] This disclosure generally relates to methods for chemically strengthening glass articles, and more specifically, to methods for chemically strengthening glass articles using alkali metal acetates. Background Technology
[0002] Glass substrates are commonly used in display devices, such as liquid crystal displays (LCDs), electrophoretic displays (EPDs), organic light-emitting diode displays (OLEDs), plasma display panels (PDPs), or the like.
[0003] Glass-based materials are known to be used as components in consumer electronic devices that include displays. Furthermore, it is known to chemically strengthen glass-based materials through ion exchange with nitrates. However, there is a need to develop new methods for forming chemically strengthened glass-based articles. Summary of the Invention
[0004] This article describes a method for chemically strengthening glass articles. A mixture of alkali metal acetates and alkali metal carbonates can be used to chemically strengthen glass articles. Providing a molten salt solution as a mixture of alkali metal acetates and alkali metal carbonates simplifies the disposal and / or waste disposal costs associated with the mixture because it is non-explosive and / or more environmentally friendly compared to alkali metal nitrates. Furthermore, alkali metal acetates and alkali metal carbonates can be cheaper than alkali metal nitrates. Additionally, a molten salt solution of a mixture of alkali metal acetates and alkali metal carbonates can reduce greenhouse gas emissions compared to a comparative molten salt solution consisting only of alkali metal nitrates, because the molten salt solution of the mixture can be formed at a lower temperature than the comparative molten salt solution, and the molten salt solution of the mixture does not produce the same level of nitrogen oxides (NOx) or other greenhouse gases as the comparative molten salt solution during use in chemically strengthening glass articles. Furthermore, as illustrated in the examples herein, the molten salt solution of the mixture can limit the reduction of compressive stress formed in the continuous chemical strengthening process of continuous glass articles, compared to a molten salt solution formed solely by alkali metal nitrates, for example, by the reaction of carbonates in the mixture with lithium ions exchanged from the glass articles into the molten salt solution.
[0005] Without being bound by theory, we believe that adding alkali metal carbonates will shift the thermodynamic equilibrium towards potassium acetate, thereby reducing the thermal decomposition of alkali metal acetates (compared to potassium acetate alone). Furthermore, without being bound by theory, we believe that adding more than 5% by weight (e.g., from 5% to 20% by weight, or from 8% to 15% by weight) of carbonate may exceed the amount of carbonate formed from a molten alkali metal acetate solution. Thus, the composition obtained according to this disclosure by heating a mixture of alkali metal acetates and alkali metal carbonates may not be formed from the thermal decomposition of a molten alkali metal acetate solution. Moreover, starting with a mixture of alkali metal acetates and alkali metal carbonates can reduce the amount of residue formed, because the mixture is considered closer to equilibrium than a molten alkali metal acetate solution.
[0006] Providing the molten salt solution with temperatures below or equal to 475°C, 400°C, and / or 345°C can reduce the amount of thermal decomposition of alkali metal acetates, which can increase the service life of the molten salt solution. Providing a initial temperature below or equal to 350°C can prevent... Figure 11-13 Most of the thermal degradation observed here can further increase the stability and / or lifespan of the molten salt solution at the corresponding temperature. As the examples here demonstrate, providing a mixture of alkali metal acetates and alkali metal carbonates as raw materials and / or in the molten salt solution increases the thermal stability of the corresponding molten salt solution.
[0007] The following describes some examples of aspects of this disclosure. It should be understood that any feature of the various aspects can be used alone or in combination with each other.
[0008] Aspect 1. A method for chemically strengthening glass articles, comprising:
[0009] The glass article is contacted with a molten salt solution comprising alkali metal acetates and alkali metal carbonates, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C to less than or equal to 475°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article including a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa to less than or equal to 1500 MPa.
[0010] Prior to the contact, the glass article comprises lithium, and the immersion chemically strengthens the glass article by ion exchange between the lithium in the glass article and potassium in the molten salt solution.
[0011] Aspect 2. The method according to aspect 1 further includes heating the mixture of the alkali metal acetate and the alkali metal carbonate to the first temperature prior to the contact, wherein the heating melts the mixture to form the molten salt solution.
[0012] Aspect 3. A method for chemically strengthening glass articles, comprising:
[0013] A mixture of alkali metal acetate and alkali metal carbonate is heated to a first temperature, wherein the heating melts the mixture to form a molten salt solution; and
[0014] The glass article is brought into contact with a molten salt solution comprising the alkali metal acetate and the alkali metal carbonate, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C to less than or equal to 475°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article comprising a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa to less than or equal to 1500 MPa.
[0015] Aspect 4. The method according to any one of Aspects 2 to 3, wherein the mixture of the alkali metal acetate and the alkali metal carbonate comprises, based on 100% by weight of the mixture:
[0016] The alkali metal acetates from 80% to 95% by weight; and
[0017] The alkali metal carbonates range from 5% or more by weight to 20% or less by weight.
[0018] Aspect 5. The method according to any one of Aspects 1 to 4, wherein the molten salt solution exhibits a weight loss of less than or equal to 5.5% by weight when maintained at the first temperature for 10 days without the contact.
[0019] A method for chemically strengthening glass articles, comprising:
[0020] The glass article is contacted with a molten salt solution comprising alkali metal acetates and alkali metal carbonates, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C and less than or equal to 345°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article including a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa and less than or equal to 1500 MPa.
[0021] The molten salt solution exhibits a weight loss of less than or equal to 5.5% by weight when maintained at the first temperature for 10 days without the contact.
[0022] Aspect 7. The method according to any one of Aspects 1 to 6, wherein the molten salt solution comprises, based on 100% by weight of the molten salt solution:
[0023] The alkali metal acetates from 80% to 95% by weight; and
[0024] The alkali metal carbonates range from 5% or more by weight to 20% or less by weight.
[0025] Aspect 8. The method according to any one of Aspects 1 to 7, wherein the total amount of the alkali metal acetate and the alkali metal carbonate in the molten salt solution is equal to 100% by weight of the molten salt solution.
[0026] Aspect 9. The method according to any one of Aspects 1 to 8, wherein the alkali metal acetate is potassium acetate and the alkali metal carbonate is potassium carbonate.
[0027] Aspect 10. The method according to any one of Aspects 1 to 9, wherein the alkali metal acetate is sodium acetate and the alkali metal carbonate is sodium carbonate.
[0028] Aspect 11. The method according to any one of Aspects 1 to 9, wherein the alkali metal acetate is a combination of sodium acetate and potassium acetate, and the alkali metal carbonate is a combination of sodium carbonate and potassium carbonate.
[0029] Aspect 12. The method according to aspect 11, wherein the weight % ratio of potassium to sodium in the molten salt solution is from 66:33 to 99:1.
[0030] Aspect 13. The method according to any one of Aspects 1 to 12, wherein the pH of the sample of said molten salt solution is from greater than or equal to 10.0 to less than or equal to 11.2.
[0031] Aspect 14. The method according to any one of Aspects 1 to 13, wherein the first temperature is from greater than or equal to 310°C to less than or equal to 400°C.
[0032] Aspect 15. The method according to aspect 14, wherein the first temperature is from greater than or equal to 320°C to less than or equal to 345°C.
[0033] Aspect 16. The method according to any one of Aspects 1 to 15, wherein the first time period is from greater than or equal to 5 minutes to less than or equal to 96 hours.
[0034] Aspect 17. The method according to any one of Aspects 1 to 16, wherein the contact comprises immersing the glass article in a molten salt bath containing the molten salt solution, and the contact forms a lithium carbonate precipitate deposited at the bottom of the molten salt bath.
[0035] Aspect 18. The method according to any one of Aspects 1 to 17, wherein the maximum compressive stress is from greater than or equal to 800 MPa to less than or equal to 1200 MPa.
[0036] Aspect 19. The method according to any one of Aspects 1 to 18, wherein the composition corresponding to the body of the glass article comprises, based on 100 mol% of the composition:
[0037] From greater than or equal to 50 mol% to less than or equal to 80 mol% of SiO2;
[0038] Al2O3 ranging from greater than or equal to 1 mol% to less than or equal to 30 mol%;
[0039] From greater than or equal to 0 mol% to less than or equal to 10 mol% of B2O3;
[0040] P2O5 from greater than or equal to 0 mol% to less than or equal to 15 mol%;
[0041] Li₂O from ≥2 mol% to ≤40 mol%; and
[0042] RO ranges from greater than or equal to 0 mol% to less than or equal to 30 mol%, where RO is the total amount of MgO, CaO, SrO, BaO, and ZnO.
[0043] Aspect 20. The method according to aspect 19, wherein the composition corresponding to the body of the glass article comprises:
[0044] From 52 mol% or more to 70 mol% of SiO2;
[0045] Al2O3 ranging from 5 mol% to 20 mol%;
[0046] From 5 mol% to 25 mol% of Li₂O;
[0047] B2O3 from greater than or equal to 0 mol% to less than or equal to 8 mol%;
[0048] From greater than or equal to 0 mol% to less than or equal to 5 mol% of P2O5; and
[0049] RO from greater than or equal to 1 mol% to less than or equal to 20 mol%.
[0050] Aspect 21. The method according to any one of Aspects 19 to 20, wherein the composition corresponding to the body of the glass article further comprises from greater than or equal to 1.0 mol% to less than or equal to 12 mol% of Na2O.
[0051] Aspect 22. The method according to any one of Aspects 1 to 21, wherein the glass article is unstrengthened prior to the contact.
[0052] Aspect 23. The method according to any one of Aspects 1 to 22 further includes contacting the chemically strengthened glass article with a second molten salt solution, the second molten salt solution being maintained at a second temperature of greater than or equal to 295°C to less than or equal to 475°C for a second time period of greater than or equal to 1 minute to less than or equal to 24 hours, wherein the second molten salt solution comprises potassium acetate and potassium carbonate, and the molten salt solution that contacted the glass article prior to the second molten salt solution comprises sodium acetate and sodium carbonate.
[0053] Aspect 24. The method according to aspect 23, wherein the second molten salt solution further comprises sodium acetate and sodium carbonate.
[0054] Aspect 25. The method according to aspect 24, wherein the molten salt solution that contacts the glass article before the second molten salt solution further comprises potassium acetate and potassium carbonate.
[0055] Aspect 26. The method according to any one of Aspects 1 to 22 further comprises contacting the chemically strengthened glass article with a second molten salt solution, the second molten salt solution being maintained at a second temperature of greater than or equal to 330°C to less than or equal to 530°C for a second time period of greater than or equal to 1 minute to less than or equal to 24 hours, wherein the second molten salt solution comprises potassium nitrate, and the molten salt solution that contacted the glass article prior to the second molten salt solution comprises sodium acetate and sodium carbonate.
[0056] Aspect 27. The method according to aspect 27, wherein the molten salt solution that contacts the glass article before the second molten salt solution further comprises potassium acetate and potassium carbonate.
[0057] Aspect 28. The method according to any one of Aspects 1 to 27 further comprises heating the glass article at an initial temperature of greater than or equal to 200°C to less than or equal to 300°C for a period of time from greater than or equal to 10 minutes to less than or equal to 24 hours prior to the contact, wherein the contact occurs immediately after the heating of the glass article.
[0058] Aspect 29. The method according to any one of Aspects 1 to 28, wherein the chemically strengthened glass article has a B10 failure strength greater than or equal to 1380 MPa in a ring-to-ring test.
[0059] Throughout this disclosure, the accompanying drawings are used to emphasize certain aspects. Therefore, unless explicitly stated otherwise, the relative sizes of the different areas, portions, and substrates shown in the drawings should not be assumed to be proportional to their actual relative sizes. Attached Figure Description
[0060] The above and other features and advantages of this disclosure will be better understood when the following detailed description is read with reference to the accompanying drawings, in which:
[0061] Figure 1 It is a schematic plan view of a consumer electronic device based on examples from various aspects;
[0062] Figure 2 yes Figure 1 A schematic perspective view of an example consumer electronic device;
[0063] Figure 3 This is a schematic 3D diagram of a foldable consumer electronics product;
[0064] Figure 4 This is a flowchart illustrating an example method for producing a chemically strengthened glass article according to aspects of this disclosure;
[0065] Figure 5 A step in a method for chemically strengthening glass articles is schematically shown, the step comprising heating a mixture of alkali metal acetate and alkali metal carbonate to form a molten salt solution;
[0066] Figure 6 A step in a method of chemically strengthening glass articles is schematically shown, the step including heating the glass articles;
[0067] Figure 7 A step in a method of chemically strengthening glass articles is schematically shown, the step comprising contacting the glass articles with a molten salt solution;
[0068] Figure 8 A step in a method for chemically strengthening glass articles is schematically shown, the step comprising contacting the glass article with a second molten salt solution;
[0069] Figure 9 The diagram schematically illustrates chemically strengthened glass articles that can be produced according to the method of this disclosure;
[0070] Figure 10 The illustration schematically shows that, according to aspects of this disclosure, for a molten salt solution or its components, the infrared transmittance (T%) on the vertical axis (i.e., the y-axis) varies with the infrared transmittance on the horizontal axis (i.e., the x-axis) in centimeters. -1 (cm) -1 The value varies in wavenumber (WN) in units of 0.
[0071] Figure 11 The diagram illustrates that, according to aspects of this disclosure, for raw materials used to form a molten salt solution, the weight loss (WT%) on the left vertical axis and the heat flux (HF) in milliwatts per milligram (mW / mg) on the right vertical axis vary with the temperature (T) in °C on the horizontal axis (i.e., the x-axis).
[0072] Figure 12 The diagram illustrates, according to aspects of this disclosure, that for a component formed in a molten salt solution, the weight loss (WT%) on the left vertical axis and the heat flux (HF) in milliwatts per milligram (mW / mg) on the right vertical axis vary with the temperature (T) in °C on the horizontal axis (i.e., the x-axis).
[0073] Figure 13 The diagram illustrates that, according to aspects of this disclosure, for the molten salt solution used, the weight loss (WT%) on the left vertical axis and the heat flux (HF) in milliwatts per milligram (mW / mg) on the right vertical axis vary with the temperature (T) in °C on the horizontal axis (i.e., the x-axis).
[0074] Figure 14 The Weibull distribution of chemically strengthened glass articles is schematically illustrated, showing the percentage of failure (F%) on the vertical axis (i.e., the y-axis) as a function of the failure strength (S) in ring-to-ring tests on the horizontal axis (i.e., the x-axis), with the B10 failure strength marked.
[0075] Figure 15 The stress distribution is schematically shown, where the compressive stress (CS) on the vertical axis (i.e., the y-axis) varies with the depth (d) on the horizontal axis (i.e., the x-axis) from the surface of the chemically strengthened glass article in micrometers (µm).
[0076] Throughout this disclosure, the accompanying drawings are used to emphasize certain aspects. Therefore, unless explicitly stated otherwise, the relative sizes of the different areas, portions, and substrates shown in the drawings should not be assumed to be proportional to their actual relative sizes. Detailed Implementation
[0077] The aspects will now be described more fully below with reference to the accompanying drawings, which illustrate example aspects. Where possible, the same reference numerals are used throughout the drawings to refer to the same or similar parts. However, the claims may cover many different aspects among a variety of aspects and should not be construed as limited to those stated herein.
[0078] Figure 9 Chemically strengthened glass article 901 is schematically shown. Figure 1-3A schematic diagram of consumer electronic devices 100 and / or 301 is shown. Unless otherwise indicated, descriptions of features of various aspects of a chemically strengthened glass article and / or its manufacturing method are equally applicable to corresponding features of any aspect of this disclosure. For example, the same part numbers throughout this disclosure may indicate that features identified in some aspects are identical to each other, and unless otherwise indicated, descriptions of features identified in one aspect are equally applicable to features identified in any other aspect of this disclosure.
[0079] This disclosure may include consumer electronic devices. Consumer electronic devices may include a front surface, a back surface, and side surfaces. Consumer electronic devices may further include electrical components at least partially located within a housing. The electrical components may include a controller, memory, and a display. The display may be located at or adjacent to the front surface of the housing. The display may include a liquid crystal display (LCD), an electrophoretic display (EPD), an organic light-emitting diode (OLED) display, or a plasma display panel (PDP). Consumer electronic devices may include a cover substrate disposed above the display. In various aspects, at least one of the housing or the cover substrate includes a chemically strengthened glass article 901 (see [link to relevant documentation]) throughout the discussion of this disclosure. Figure 1-3 (and 9). Consumer electronic devices may include in-vehicle displays or portable electronic devices, such as smartphones, tablets, wearable devices, or laptops.
[0080] Chemically strengthened glass articles 901 can be incorporated into another article, such as articles having a display (or display articles) (e.g., consumer electronic devices, including mobile phones, tablet computers, computers, navigation systems, wearable devices (e.g., watches), and the like), building articles, transportation articles (e.g., automobiles, trains, aircraft, ships, etc.), electrical articles, or any article that may benefit from some transparency, scratch resistance, abrasion resistance, or a combination thereof. Exemplary articles incorporating any chemically strengthened glass article 901 disclosed herein are... Figure 1-2 shown in . Specifically, Figure 1-2 A consumer electronic device 100 is shown, comprising a housing 102 having a front surface 104, a back surface 106, and side surfaces 108. Although not shown, the consumer electronic device may include electrical components at least partially or entirely within the housing. For example, the electrical components include at least a controller, memory, and a display. Figure 1-2As shown, the display 110 may be located at or adjacent to the front surface of the housing 102. A consumer electronic device may include a cover substrate 112 at or above the front surface of the housing 102, such that the cover substrate is above the display 110. In various aspects, at least one of the cover substrate 112 or a portion of the housing 102 may comprise any of the chemically strengthened glass articles 901 disclosed herein.
[0081] also, Figure 3 A perspective view of a foldable consumer electronic device 301 is schematically shown. The consumer electronic device 301 may include a chemically strengthened glass article 901 according to aspects of this disclosure. As shown, the consumer electronic device 301 may include a front surface 303 and a side surface 305. The consumer electronic device 301 may include electronic components, including a display 302 viewable through the front surface 303. In various aspects, as shown, the consumer electronic device 301 can be folded along direction 312 to form a folded configuration that brings the first end 327 and the second end 337 (opposite to the first end 327) closer together (compared to an unfolded configuration). Additionally, as shown, the consumer electronic device 301 can be folded such that the front surface 303 and / or the display 302 face itself, but the consumer electronic device can also be folded in the opposite direction 312 such that the front surface 303 is on the outside of the consumer electronic device in the folded configuration. Figure 3 The consumer electronic device 301 shown can be folded about a folding axis 382, with the central portion 381 located between a first portion 332 containing a first end 327 and a second portion 331 containing a second end 337. The position of the folding axis 382 can be determined relative to a second distance 315 (e.g., along direction 308) between the second end 337 and the folding axis 382, defining a first distance 313 (e.g., along direction 306) between the first end 327 and the folding axis 382. The total length of the consumer electronic device can be the sum of the first distance 313 and the second distance 315. The width 307 of the consumer electronic device 301 is measured along a direction 304 perpendicular to direction 306. Furthermore, as shown, the consumer electronic device is depicted in a folded or partially folded configuration, with the front surface 303 forming an angle A about the folding axis 382. Figure 3As shown, the consumer electronic device 301 may include a chemically strengthened glass article 901, which may include a single folding axis to allow the corresponding article to form a bifold structure, wherein, for example, the corresponding article can be folded in half. In a further aspect, the consumer electronic device 301 may include a chemically strengthened glass article 901, which may include two or more folding axes, wherein, for example, each folding axis includes a corresponding central portion similar to or identical to the central portion discussed herein. For example, providing two folding axes may allow the consumer electronic device 301 to include a chemically strengthened glass article 901 to form a trifold structure, wherein, for example, the corresponding article can be folded to have a first portion, a second portion, and a third portion similar to or identical to the first or second portion, wherein a central portion and another central portion similar to or identical to the central portion are respectively positioned between the first and second portions and between the second and third portions.
[0082] Chemically strengthened glass-based article 901 may include glass-based article 911, which comprises a glass-based material having a pencil hardness of 8H or higher, such as 9H or higher. As used herein, “glass-based” includes glass and glass-ceramics, wherein the glass-ceramics have one or more crystalline phases and an amorphous residual glass phase. Glass-based materials (e.g., glass-based substrates) may include amorphous materials (e.g., glass) and optionally one or more crystalline materials (e.g., ceramics). Amorphous materials and glass-based materials may be strengthened. As used herein, the term “strengthened” may refer to a material that has been chemically strengthened, for example by ion exchange of smaller ions on the substrate surface with larger ions, as discussed below. However, other strengthening methods may be used, such as thermal tempering, or by utilizing the mismatch in the coefficients of thermal expansion between different portions of the substrate to create compressive stress and a central tension zone, thereby forming a strengthened substrate. Exemplary glass-based materials that may be lithium-free or contain lithium oxide include soda-lime glass, alkali aluminosilicate glass, alkali borosilicate glass, alkali aluminosilicate glass, alkali phosphosilicate glass, and alkali aluminosilicate glass. "Glass-ceramics" encompass materials produced through the controlled crystallization of glass. In all respects, glass-ceramics have a crystallinity of about 1% to about 99%. Examples of suitable glass-ceramics may include Li₂O-Al₂O₃-SiO₂ (i.e., LAS-based) glass-ceramics, MgO-Al₂O₃-SiO₂ (i.e., MAS-based) glass-ceramics, ZnO × Al₂O₃ × nSiO₂ (i.e., ZAS-based) glass-ceramics, and / or glass-ceramics comprising a major crystalline phase, said major crystalline phase comprising β-quartz solid solution, β-spodumene, cordierite, penelopecerite, and / or lithium disilicate. Glass-ceramic substrates can be strengthened using chemical strengthening processes as described herein. As used herein, "ceramic system" includes ceramics and glass-ceramics, wherein the glass-ceramic has one or more crystalline phases and an amorphous residual glass phase. Ceramic-system materials can be strengthened (e.g., chemically strengthened). In all respects, ceramic-system materials can be formed by heating a glass-system material to form a ceramic (e.g., crystalline) portion.
[0083] In various aspects, the chemically strengthened glass article 901 may include lithium and / or alkali aluminosilicate glass. In various aspects, based on 100 mol% of the chemically strengthened glass article 901, the composition may include: SiO2 from ≥40 mol% to ≤80 mol%; Al2O3 from ≥1 mol% to ≤30 mol%; Li2O and / or R2O from ≥2 mol% to ≤40 mol%; and optionally: RO from ≥0 mol% to ≤30 mol%; B2O3 from ≥0 mol% to ≤10 mol%; P2O5 from ≥0 mol% to ≤15 mol%; and / or ZrO2 from ≥0 mol% to ≤5 mol%. As used herein, “RO” refers to the total amount of MgO, CaO, SrO, and BaO. As used herein, “R2O” refers to the total amount of Li2O, Na2O, K2O, Cs2O, and Rb2O. In a further aspect, the composition of the chemically strengthened glass article 901 may include: SiO2 from greater than or equal to 52 mol% to less than or equal to 70 mol%, Al2O3 from greater than or equal to 5 mol% to less than or equal to 20 mol%, Li2O and / or R2O from greater than or equal to 5 mol% to less than or equal to 25 mol%, RO from greater than or equal to 1 mol% to less than or equal to 20 mol%, B2O3 from greater than or equal to 0 mol% to less than or equal to 8 mol%, and / or P2O5 from greater than or equal to 0 mol% to less than or equal to 5 mol%. In a further aspect, the composition of the chemically strengthened glass article 901 may further include: Na2O from greater than or equal to 1.0 mol% to less than or equal to 12 mol%, Li2O from greater than or equal to 5 mol% to less than or equal to 25 mol%, and / or K2O from greater than or equal to 0 mol% to less than or equal to 0.5 mol%. In a further aspect, the composition of the chemically strengthened glass article 901 may include: SiO2 from 60 mol% to 70 mol%, Al2O3 from 8 mol% to 16 mol%, Li2O and / or R2O from 12 mol% to 20 mol%, RO from 2 mol% to 6 mol%, optionally B2O3 from 0 mol% to 5 mol% and / or P2O5 from 0 mol% to 2 mol%, and optionally K2O from 0 mol% to 1 mol%. In a further aspect, Al2O3-R2O may be from -6.0 mol% to -2.0 mol% or from -5.8 mol% to -2.2 mol%.In all respects, chemically strengthened glass articles 901 may be free of one or more of P2O5, TiO2, ZnO, ZrO2, Ta2O5, HfO2, La2O3, and / or Y2O3. Unless otherwise specified, as used herein, the term "free of" does not require absolute precision or atomic accuracy, and means that the component may be present in very small amounts (e.g., as a contaminant, for example, less than 0.1 mol%) in the final glass composition, which a reasonable practitioner can practically achieve, and in some respects does indeed contain 0.0 mol%. For example, the inclusion of ZrO2 in a glass composition may result in the formation of undesirable zirconium oxide inclusions in the glass material, at least in part due to the low solubility of ZrO2 in the glass material. Furthermore, the inclusion of Ta2O5, HfO2, La2O3, and / or Y2O3 may increase the cost of raw materials associated with the glass substrate.
[0084] In all respects, chemically strengthened glass articles 901 can be optically transparent. As used herein, “transparent,” “optically transparent,” or “optically clear” means an average transmittance of 70% or higher in the wavelength range of 400 nm to 700 nm through a 1.0 mm thick sheet of material. In all respects, “optically transparent material” or “optically clear material” may have an average transmittance of 75% or higher, 80% or higher, 85% or higher, or 90% or higher, 92% or higher, 94% or higher, or 96% or higher in the wavelength range of 400 nm to 700 nm through a 1.0 mm thick sheet of material. The average transmittance in the wavelength range of 400 nm to 700 nm is calculated by measuring the transmittance at integer wavelengths from 400 nm to 700 nm and averaging the measurements.
[0085] Throughout this disclosure, the Young's modulus of glass materials is measured using the resonant ultrasonic spectroscopy technique described in ASTM E2001-13, entitled "Standard Guide for Resonant Ultrasound Spectroscopy for Defect Detection in Both Metallic and Non-metallic Parts". In various aspects, chemically strengthened glass articles 901 may include an elastic modulus of 50 GPa or higher, 60 GPa or higher, 65 GPa or higher, 70 GPa or higher, 72 GPa or higher, 75 GPa or higher, 120 GPa or lower, 100 GPa or lower, 90 GPa or lower, 80 GPa or lower, 75 GPa or lower, 72 GPa or lower, or 70 GPa or lower. In a further aspect, chemically strengthened glass article 901 may include a glass material having an elastic modulus ranging from 50 GPa to 120 GPa, from 60 GPa to 100 GPa, from 65 GPa to 90 GPa, from 70 GPa to 80 GPa, from 72 GPa to 75 GPa, or any range or subrange thereof.
[0086] like Figure 9As shown, a chemically strengthened glass article 901 may include a first main surface 903 and a second main surface 905 opposite to the first main surface 903. In various aspects, the first main surface 903 may extend along a first plane, and / or the second main surface 905 may extend along a second plane. In a further aspect, the second plane (second main surface 905) may be parallel to the first plane (first main surface 903). As used herein, the article thickness 909 of the chemically strengthened glass article 901 is defined as the average distance between the first main surface 903 and the second main surface 905. In all respects, the article thickness 909 can be 25 micrometers (µm) or greater, 30 µm or greater, 40 µm or greater, 50 µm or greater, 60 µm or greater, 80 µm or greater, 100 µm or greater, 300 µm or greater, 500 µm or greater, 1 millimeter (mm) or greater, 5 mm or less, 3 mm or less, 2 mm or less, 1 mm or less, 800 µm or less, 600 µm or less, 400 µm or less, 300 µm or less, 250 µm or less, 200 µm or less, 160 µm or less, 120 µm or less, 100 µm or less, 80 µm or less, 60 µm or less, 50 µm or less, or 40 µm or less. In all respects, the article thickness 909 can be from 25 µm to 5 mm, from 30 µm to 3 mm, from 40 µm to 2 mm, from 60 µm to 1 mm, from 80 µm to 800 µm, from 100 µm to 600 µm, from 300 µm to 400 µm, or any range or subrange thereof. In all respects, the chemically strengthened glass article 901 can be an ultrathin substrate, meaning that the article thickness 909 is 300 micrometers or less, for example, from 25 µm to 300 µm, from 30 µm to 250 µm, from 40 µm to 200 µm, from 50 µm to 160 µm, from 60 µm to 120 µm, from 80 µm to 100 µm, or any range or subrange thereof. In various aspects, as shown in the figure, the local thickness of the chemically strengthened glass article 901 can be substantially uniform on the first main surface 903 and / or the second main surface 905 (e.g., substantially equal to the article thickness 909).
[0087] Chemically strengthened glass article 901 may include one or more compressive stress zones. In various respects, compressive stress zones can be generated by chemical strengthening. Chemical strengthening may include an ion exchange process in which ions in the surface layer are replaced or exchanged by larger ions having the same valence or oxidation state. Methods of chemical strengthening will be discussed later. Without being bound by theory, chemically strengthened glass articles forming chemically strengthened glass article 901 can achieve good impact resistance and / or puncture resistance (e.g., not failing when a pen is dropped from a height of 20 cm). Without being bound by theory, chemically strengthened glass articles can achieve small (e.g., 10 mm or less) bending radii because the compressive stress from chemical strengthening can offset the tensile stress induced by bending on the outermost surface of the substrate. The compressive stress zone may extend into a portion of the glass article 901, reaching a depth referred to as the compression depth. As used herein, compression depth means the depth at which the stress in the chemically strengthened substrate and / or portion described herein changes from compressive stress to tensile stress. Depending on the ion exchange treatment and the thickness of the article being measured, the compression depth can be measured using a surface stress meter or a scattered light polarizer (SCALP, where the values reported herein are obtained using the SCALP-5 manufactured by Glassstress, Estonia). In cases where stress is generated in the substrate and / or portions thereof by exchanging potassium ions into the substrate, the compression depth is measured using a surface stress meter, such as the FSM-6000 (Orihara Industrial Co., Ltd. (Japan)). Unless otherwise specified, compressive stress (including surface CS) is measured using commercially available instruments via a surface stress meter (FSM) such as the FSM-6000 manufactured by Orihara. Surface stress measurement relies on the accurate measurement of the stress optical coefficient (SOC) associated with the birefringence of the glass. Unless otherwise specified, SOC is measured according to Procedure C (Glass Disk Method) as described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein by reference in their entirety. When stress is generated by exchanging sodium ions into the substrate and the article thickness being measured is greater than 400 µm, the depth of compression and center tension (CT) are measured using SCALP. When stress is generated in the substrate and / or portions by exchanging both potassium and sodium ions into the substrate and / or portions thereof, and the article thickness being measured is greater than 400 µm, the depth of compression and CT are measured by SCALP.Without being bound by theory, the exchange depth of sodium ions can indicate the compressive depth, while the exchange depth of potassium ions can indicate a change in the magnitude of compressive stress (rather than a change in stress from compression to tension). A refractive near-field (RNF) method can also be used to derive a graphical representation of the stress distribution. When deriving a graphical representation of the stress distribution using the RNF method, the maximum center tension value provided by SCALP is utilized in the RNF method. The graphical representation of the stress distribution derived from the RNF is force-balanced and calibrated based on the maximum center tension value provided by SCALP measurement. As used herein, “layer depth” (DOL) refers to the depth to which ions (e.g., sodium, potassium) have been exchanged into the substrate and / or portion thereof. According to this disclosure, when the maximum center tension cannot be directly measured by SCALP (e.g., when the thickness of the article being measured is less than 400 µm), the maximum center tension can be approximated by dividing the product of the maximum compressive stress and the compression depth by the difference between the substrate thickness and twice the compression depth, wherein the compressive stress and compression depth are measured by FSM. Throughout this disclosure, the absolute value of the compressive stress is reported as the compressive stress, and the absolute value of the center tensile stress is reported as the center tensile stress.
[0088] In all aspects, such as Figure 9 As shown, the first primary surface 903 of a chemically strengthened glass article 901 may include a first compressive stress region 912 extending from the first primary surface 903 to a first compressive depth 913. Although not shown, the first compressive stress region 912 may also include a first layer depth of one or more alkali metal ions (e.g., potassium) associated with the first compressive stress region. In various aspects, as Figure 9 As shown, the second primary surface 905 of the chemically strengthened glass article 901 may include a second compressive stress region 904 extending from the second primary surface 905 to a second compressive depth 915. Although not shown, the second compressive stress region 904 may also include a second layer depth of one or more alkali metal ions (e.g., potassium) associated with the first compressive stress region. Figure 9 As shown, dashed lines 923 and 925 correspond to the locations in chemically strengthened glass products where stress switches from compression to tension (or vice versa), and correspond to the boundaries of the corresponding compressive stress zones (i.e., compression depths).
[0089] In all respects, the percentage of the first compression depth 913 and / or the second compression depth 915 to the article thickness 909 may be 5% or greater, 10% or greater, 12% or greater, 14% or greater, 16% or greater, 18% or greater, 20% or greater, 30% or less, 26% or less, or 22% or less, 20% or less, 19% or less, 18% or less, 17% or less, or 16% or less. In all respects, the percentage of the first compression depth 913 and / or the second compression depth 915 to the article thickness 909 may range from 5% to 30%, from 10% to 26%, from 12% to 22%, from 14% to 20%, from 16% to 19%, from 16% to 19%, from 16% to 18%, or any range or subrange thereof. In all aspects, the percentage of the first compression depth 913 and / or the second compression depth 915 to the article thickness 909 can be 15% or greater, for example, from 16% to 30%, from 16% to 26%, from 18% to 24%, from 20% to 22%, or any range or subrange therebetween. In an exemplary aspect, the percentage of the first compression depth 913 and / or the second compression depth 915 to the article thickness 909 can be from 10% to 30%, from 12% to 19%, or from 16% to 26%. In all respects, the first compression depth 913 and / or the second compression depth 915 may be 5 µm or greater, 6 µm or greater, 7 µm or greater, 8 µm or greater, 10 µm or greater, 12 µm or greater, 15 µm or greater, 20 µm or greater, 25 µm or greater, 30 µm or greater, 400 µm or less, 300 µm or less, 200 µm or less, 100 µm or less, 50 µm or less, 30 µm or less, 20 µm or less, 10 µm or less, 9 µm or less, 8 µm or less, or 7 µm or less. In all aspects, the range of the first compression depth 913 and / or the second compression depth 915 may be from 5 µm to 500 µm, from 6 µm to 400 µm, from 7 µm to 300 µm, from 8 µm to 200 µm, from 10 µm to 100 µm, from 12 µm to 50 µm, or any range or subrange thereof. In all aspects, the first compression depth 913 and / or the second compression depth 915 may be from greater than or equal to 5 µm to less than or equal to 30% of the substrate thickness, from greater than or equal to 7 µm to less than or equal to 25% of the substrate thickness, from greater than or equal to 10 µm to less than or equal to 20% of the substrate thickness, from greater than or equal to 12 µm to less than or equal to 18% of the substrate thickness, from greater than or equal to 15 µm to less than or equal to 15% of the substrate thickness, or any range or subrange thereof.
[0090] In all respects, the percentage of the first and / or second layer depth of one or more alkali metal ions (e.g., potassium) to the article thickness 909 can be 5% or greater, 10% or greater, 12% or greater, 14% or greater, 16% or greater, 18% or greater, 20% or greater, 30% or less, 26% or less, or 22% or less, 20% or less, 19% or less, 18% or less, 17% or less, or 16% or less. In all respects, the percentage of the first and / or second layer depth of one or more alkali metal ions (e.g., potassium) to the article thickness 909 can range from 5% to 30%, from 10% to 26%, from 12% to 22%, from 14% to 20%, from 16% to 19%, from 17% to 18%, or any range or subrange thereof. In all aspects, the percentage of the first and / or second layer depth of one or more alkali metal ions (e.g., potassium) to the article thickness 909 can be 15% or greater, for example, ranging from 16% to 30%, from 16% to 26%, from 18% to 24%, from 20% to 22%, or any range or subrange therebetween. In a preferred aspect, the percentage of the first and / or second layer depth of one or more alkali metal ions (e.g., potassium) to the article thickness 909 can range from 10% to 30%, from 12% to 19%, or from 16% to 26%. In all respects, the first layer depth and / or second layer depth of one or more alkali metal ions (e.g., potassium) may be 3 µm or greater, 5 µm or greater, 7 µm or greater, 10 µm or greater, 15 µm or greater, 20 µm or greater, 25 µm or greater, 30 µm or greater, 35 µm or greater, 100 µm or less, 60 µm or less, 50 µm or less, 40 µm or less, 30 µm or less, 25 µm or less, 20 µm or less, 15 µm or less, 10 µm or less, or 8 µm or less. In all respects, the first layer depth and / or second layer depth of one or more alkali metal ions (e.g., potassium) can range from 3 µm to 100 µm, from 5 µm to 60 µm, from 7 µm to 50 µm, from 10 µm to 40 µm, from 15 µm to 35 µm, from 20 µm to 30 µm, or any range or subrange thereof.
[0091] In various aspects, the first compressive stress zone 912 may include a first maximum compressive stress, and / or the second compressive stress zone 904 may include a second maximum compressive stress. In a further aspect, the first maximum compressive stress may be substantially equal to the second maximum compressive stress. In a further aspect, the first maximum compressive stress and / or the second maximum compressive stress may be 400 MPa or greater, 600 MPa or greater, 700 MPa or greater, 800 MPa or greater, 900 MPa or greater, 1000 MPa or greater, 1100 MPa or greater, 1500 MPa or less, 1300 MPa or less, 1250 MPa or less, 1200 MPa or less, 1150 MPa or less, 1100 MPa or less, 1050 MPa or less, 1000 MPa or less, 950 MPa or less, 900 MPa or less, or 850 MPa or less. In a further aspect, the range of the first maximum compressive stress and / or the second maximum compressive stress can be any range or subrange between 400 MPa and 1500 MPa, 600 MPa and 1300 MPa, 700 MPa and 1250 MPa, 800 MPa and 1200 MPa, 900 MPa and 1150 MPa, 1000 MPa and 1100 MPa, or any range or subrange thereof. In a preferred aspect, the range of the first maximum compressive stress and / or the second maximum compressive stress can be any range or subrange between 400 MPa and 1500 MPa, 800 MPa and 1200 MPa, 900 MPa and 1100 MPa, or any range or subrange thereof.
[0092] Throughout this disclosure, the ring-to-ring (ROR) test is a measurement of the surface strength of plate glass specimens, and ASTM C1499-09 (2013), entitled "Standard Test Method for Monotonic Equibiaxial Flexural Strength of Advanced Ceramics at Ambient Temperature," forms the basis of the ROR test method described herein. The contents of ASTM C1499-09 are incorporated herein by reference in their entirety. To determine the isobiaxial flexural strength (i.e., the maximum stress a material can withstand when flexed between two concentric rings of different sizes), the specimen is placed between two concentric rings of different sizes, with the specimen supported by a support ring having a diameter D2. A force F is applied to the surface of the glass article using a load cell with a loading ring having a diameter D1. Unless otherwise specified, the ratio of D1 / D2 is 0.5. The loading ring and the support ring are concentrically aligned within 0.5% of the diameter D2 of the support ring. The load cell used for testing is accurate within ±1% under any load within the selected range. Testing is conducted at a temperature of 23±2℃ and a relative humidity of 40±10%. For the fixture design, the radius r of the protruding surface of the loading ring is in the range of h / 2 ≤ r ≤ 3h / 2, where h is the sample thickness. The loading and support rings are made of hardened steel with a hardness HRc >40. The established failure mechanism for ROR testing is the observation of sample fracture originating from the sample surface area within the two loading rings. Failures occurring outside this area, i.e., failures between the loading and support rings, are omitted in the data analysis. However, due to the thinness and high strength of the samples, large deflections exceeding half the sample thickness h are sometimes observed. Therefore, it is not uncommon to observe a high percentage of failures originating below the loading rings. Stress cannot be accurately calculated without understanding the stress development inside and below the rings (collected through strain gauge analysis) and the failure origin in each specimen. Therefore, ROR testing primarily uses the peak load at failure as the measured response.
[0093] As used herein, "failure strength" and "ring-to-ring strength" refer to the strength measured using a ROR test. As used herein, "B10" failure strength refers to a failure strength with a probability of 10%. For example, Figure 14 The Weibull distribution of chemically strengthened glass articles is schematically illustrated by varying the failure percentile (F%) on the vertical axis 1403 (i.e., the y-axis) with the failure intensity (S) in megapascals (MPa) during ring-to-ring testing on the horizontal axis 1401 (i.e., the x-axis). Figure 14In the diagram, curves 1407 and 1417 correspond to distributions fitted to data 1405 and 1415, respectively. Furthermore, confidence intervals 1409a-1409b correspond to the distribution centered on curve 1407, and confidence intervals 1419a-1419b correspond to the distribution centered on curve 1417. The diagram shows the B10 intensities 1408 and 1418 corresponding to curves 1407 and 1417 based on data 1405 and 1415, respectively, representing the failure intensity (S) at the 10th percentile. Figure 14 In the comparative example AA, the B10 strength 1408 is 1373 MPa, and in example 1, the B10 strength 1418 is 1382 MPa. In all aspects, the B10 strength of the chemically strengthened glass article 901 can be greater than or equal to 1375 MPa, greater than or equal to 1380 MPa, or greater than or equal to 1382 MPa. In all aspects, the B10 strength exhibited by the method of this disclosure using alkali metal acetates and alkali metal carbonates is greater than or equal to the corresponding B10 strength of a comparative article chemically strengthened using alkali metal nitrates but otherwise identical to the chemically strengthened glass article, wherein the alkali metal in the corresponding molten salt solution is the same in the chemical strengthening treatment of the chemically strengthened glass article and the comparative article.
[0094] Refer to 901 for chemically strengthened glass products. Figure 4 Flowcharts and Figure 5-8 The example method steps shown in the figure and Figure 9 The cross-sectional view shown illustrates aspects of the method for chemically strengthening a chemically strengthened glass article 901 according to aspects of this disclosure.
[0095] In the first step 401 of the method disclosed herein, the method may begin by providing a glass article 611, such as Figure 6-7As shown in the figure. In various aspects, the glass article 611 can be provided by purchasing or otherwise obtaining a substrate or by forming a glass article. In various aspects, the glass article 611 may include a glass substrate. In a further aspect, the glass substrate can be provided by forming it using a variety of strip forming processes, such as groove drawing, down drawing, melt down drawing, up drawing, pressure rolling, redrawing, or floating. The glass article 611 may include an existing first main surface 603 and an existing second main surface 605 opposite to the existing first main surface 603. In a further aspect, the initial thickness 609 of the glass article 611 (defined as the average distance between the existing first main surface 603 and the existing second main surface 605) may be within one or more of the ranges discussed above and / or may be within 5 µm of the final thickness (e.g., article thickness 909) (i.e., 0.1 µm to 5 µm or 0.5 µm to 4 µm greater than the final thickness). In a further aspect, the existing first main surface 603 and / or the existing second main surface 605 may extend along a plane. In various aspects, the glass article 611 may have compositions within one or more of the ranges discussed above for the chemically strengthened glass article 901. In various aspects, at the end of step 401, the glass article 611 may be unstrengthened. As used herein, unstrengthened means that the substrate does not include layer depth, does not include compression depth, includes layer depth in the range of 0% to 5% of the substrate thickness, or includes compression depth in the range of 0% to 5% of the substrate thickness. In various aspects, at the end of step 401, the glass article 611 may include lithium and / or compositions within one or more corresponding compositional ranges discussed above for the chemically strengthened glass article 901.
[0096] In various respects, after step 401 (or step 405 discussed below), the method may proceed to step 403, which includes heating a mixture 503 of alkali metal acetate 505 and alkali metal carbonate 507 in a bath 501, as... Figure 5 As shown, to form molten salt solution 703 or 803 (see...) Figure 7-8The molten salt solution comprises a mixture of alkali metal acetates and alkali metal carbonates. In various aspects, the alkali metal acetate 505 may include sodium acetate, potassium acetate, or a combination thereof. In various aspects, the alkali metal carbonate 507 may include sodium carbonate, potassium carbonate, or a combination thereof. In various aspects, the mixture 503 and / or the molten salt solution 703 or 803 may include: (i) sodium acetate and sodium carbonate; (ii) potassium acetate and potassium carbonate; (iii) one or more of sodium acetate, potassium acetate, and sodium carbonate, potassium carbonate, or a combination thereof; or (iv) a combination of the foregoing. In a further aspect, the alkali metal acetate may be a combination of sodium acetate and potassium acetate, and the alkali metal carbonate may be a combination of sodium carbonate and potassium carbonate. In a further aspect, the weight % ratio of potassium to sodium in the mixture and / or molten salt solution can be 66:33 or greater, 75:25 or greater, 80:20 or greater, 85:15 or greater, 90:10 or greater, 95:5 or greater, 99:1 or less, 95:5 or less, 90:10 or less, 85:15 or less, 80:20 or less, or 75:25 or less, for example, from 66:33 to 99:1, from 75:25 to 95:5, from 80:20 to 90:10, from 80:20 to 85:15, or any range or subrange therebetween. In each aspect, the total amount of alkali metal acetates and alkali metal carbonates in mixture 503 and / or molten salt solution 703 or 803 can be 100% by weight of the corresponding total amount of mixture 503 and / or molten salt solution 703 or 803. In all respects, mixture 503 and / or molten salt solution 703 or 803 may consist of at least one alkali metal acetate and at least one alkali metal carbonate.
[0097] In all respects, based on 100% by weight of the mixture and / or molten salt solution, the amount of alkali metal acetate can be 80% by weight or greater, 82% by weight or greater, 85% by weight or greater, 87% by weight or greater, 90% by weight or greater, 92% by weight or greater, 95% by weight or greater, 95% by weight or less, 92% by weight or less, 90% by weight or less, 87% by weight or less, 85% by weight or less, or 82% by weight or less. In all respects, based on 100% by weight of the mixture and / or molten salt solution, the amount of alkali metal acetate can be from greater than or equal to 80% by weight to less than or equal to 95% by weight, from greater than or equal to 82% by weight to less than or equal to 92% by weight, from greater than or equal to 85% by weight to less than or equal to 90% by weight, from greater than or equal to 87% by weight to less than or equal to 90% by weight, or any range or subrange thereof. In all aspects, based on 100% by weight of the mixture and / or molten salt solution, the amount of alkali metal carbonate can be 5% by weight or more, 8% by weight or more, 9% by weight or more, 10% by weight or more, 13% by weight or more, 15% by weight or more, 18% by weight or more, 20% by weight or less, 18% by weight or less, 15% by weight or less, 13% by weight or less, 10% by weight or less, or 8% by weight or less. In all aspects, based on 100% by weight of the mixture and / or molten salt solution, the amount of alkali metal carbonate can be from greater than or equal to 5% by weight to less than or equal to 20% by weight, from greater than or equal to 8% by weight to less than or equal to 18% by weight, from greater than or equal to 10% by weight to less than or equal to 15% by weight, from greater than or equal to 10% by weight to less than or equal to 13% by weight, or any range or subrange therebetween. In all aspects, the molten salt solution may be nitrate-free.
[0098] Providing a molten salt solution as a mixture of alkali metal acetates and alkali metal carbonates simplifies the disposal and / or waste costs associated with the mixture because it is non-explosive and / or more environmentally friendly than alkali metal nitrates. Furthermore, alkali metal acetates and carbonates can be cheaper than alkali metal nitrates to a similar degree. Additionally, a molten salt solution of a mixture of alkali metal acetates and carbonates can reduce greenhouse gas emissions compared to a comparative molten salt solution consisting solely of alkali metal nitrates, because the molten salt solution of the mixture can be formed at a lower temperature than the comparative molten salt solution, and the molten salt solution of the mixture does not produce the same level of nitrogen oxides (NOx) or other greenhouse gases as the comparative molten salt solution during chemical strengthening of glass articles. Furthermore, as the examples herein demonstrate, the molten salt solution of the mixture can limit the reduction of compressive stress formed in continuous chemical strengthening processes of continuous glass articles compared to a molten salt solution formed solely of alkali metal nitrates, for example, through the reaction of carbonates in the mixture with lithium ions exchanged from the glass articles into the molten salt solution.
[0099] In some aspects, a mixture 503 of alkali metal acetate 505 and alkali metal carbonate 507 can be heated at a first temperature to obtain a molten salt solution 703 or 803. In further aspects, the first temperature can be 295°C or higher, 300°C or higher, 305°C or higher, 310°C or higher, 315°C or higher, 320°C or higher, 325°C or higher, 330°C or higher, 335°C or higher, 340°C or higher, 475°C or lower, 430°C or lower, 400°C or lower, 380°C or lower, 360°C or lower, 355°C or lower, 350°C or lower, 345°C or lower, 340°C or lower, 335°C or lower, 330°C or lower, 325°C or lower, 320°C or lower, 315°C or lower, or 310°C or lower. In a further aspect, the first temperature can be any range or subrange thereof, from 295°C to 475°C, from 300°C to 430°C, from 305°C to 400°C, from 310°C to 380°C, from 315°C to 360°C, from 320°C to 355°C, from 325°C to 350°C, from 330°C to 345°C, from 335°C to 340°C, or any range or subrange thereof. In a preferred aspect, the first temperature can be any range or subrange thereof, from 295°C to 475°C, from 310°C to 400°C, from 320°C to 345°C, or any range or subrange thereof. Providing the molten salt solution with temperatures less than or equal to 475°C, less than or equal to 400°C, and / or less than or equal to 345°C can reduce the amount of thermal decomposition of alkali metal acetates, which can increase the service life of the molten salt solution.
[0100] For example, Figure 11-13 The weight (WT%) loss on the left vertical axes 1103, 1203, and / or 1303 varies with temperature (T) in °C on the horizontal axes 1101, 1201, and / or 1301 (i.e., the x-axis) for one or more components of the molten salt solution. As shown in the figure, curves 1105, 1205, and 1305, corresponding to the wt% of the sample, show significant reductions in zones 1107, 1109, 1207, and 1307 corresponding to the thermal decomposition of the corresponding materials. Specifically, zones 1107, 1109, and / or 1307 in curves 1105 and 1305 begin above 350 °C and accelerate between 400 °C and 475 °C. Furthermore, curve 1205, corresponding to the components of the molten salt solution, has zone 1207 where the most significant reduction is observed between 350 °C and 375 °C. Therefore, providing a first temperature less than or equal to 350 °C can avoid [further damage]. Figure 11-13 Most of the thermal degradation observed can further increase the stability of the molten salt solution at the corresponding temperature and / or the service life of the molten salt solution.
[0101] The thermal stability of molten salt solutions 703 and / or 803 can be characterized by weight loss over a 10-day period, based on 100% by weight of the molten salt solution at the start of the 10-day period, wherein molten salt solutions 703 and / or 803 are maintained at a predetermined temperature. The predetermined temperature may be one or more corresponding ranges discussed above with respect to the first temperature (e.g., from 295°C to 475°C, from 310°C to 400°C, from 320°C to 345°C). Unless otherwise specified, the predetermined temperature is 340°C. In all respects, based on a 100% by weight molten salt solution at the start of a 10-day period, the weight loss exhibited by molten salt solutions 703 and / or 803 after being maintained at a predetermined temperature for 10 days is less than or equal to 5.5% by weight, less than or equal to 5.4% by weight, less than or equal to 5.3% by weight or less, less than or equal to 5.2% by weight, or less than or equal to 5.1% by weight (e.g., from 3% to 5.5% by weight, from 4% to 5.4% by weight, from 4.5% to 5.3% by weight, from 4.7% to 5.2% by weight, from 5.0% to 5.1% by weight, or any range or subrange thereof). As the examples here demonstrate, providing a mixture of alkali metal acetates and alkali metal carbonates as raw materials and / or in the molten salt solution increases the thermal stability of the corresponding molten salt solution.
[0102] As used herein, the pH of the solution is measured at 25°C according to ASTM E70-90. For molten salt solutions, the pH is determined by dissolving a cooled sample from the molten salt solution in deionized water to form a 5% by weight solution of the sample (from the molten salt solution), based on 100% by weight of the resulting solution. Without being strictly bound by theory, the pH of a 5% by weight solution of pure potassium acetate in deionized water is 8.08, and the pH of a 5% by weight solution of pure potassium carbonate in deionized water is 11.94. The pH of the molten salt solution can fall between the pH of pure potassium acetate and pure potassium carbonate. In all respects, the pH of the molten salt solution can be greater than or equal to 10.0, greater than or equal to 10.3, greater than or equal to 10.5, greater than or equal to 10.8, greater than or equal to 11.0, greater than or equal to 11.1, less than or equal to 11.2, less than or equal to 11.0, less than or equal to 10.8, less than or equal to 10.5, or less than or equal to 10.3. In all respects, the pH of the molten salt solution can be from 10.0 or 11.2 or 10.3 or 11.0 or 10.5 or 10.8 or 10.8 or any range or subrange thereof.
[0103] After step 401 or 403, the method may proceed to step 405, which includes heating the glass article 611 to an initial temperature, such as... Figure 6 As shown. In various aspects, such as Figure 6 As shown, heating the glass article 611 may include placing the glass article 611 in an environment (e.g., air, in an oven 601) that maintains an initial temperature for an initial period of time. In various aspects, the initial temperature may be 200°C or higher, 220°C or higher, 240°C or higher, 260°C or higher, 280°C or higher, 300°C or lower, 280°C or lower, 260°C or lower, 240°C or lower, or 220°C or lower. In various aspects, the initial temperature may be from greater than or equal to 200°C to less than or equal to 300°C, from greater than or equal to 220°C to less than or equal to 280°C, from greater than or equal to 240°C to less than or equal to 260°C, or any range or subrange thereof. In all aspects, the initial time period can be 10 minutes or longer, 15 minutes or longer, 30 minutes or longer, 45 minutes or longer, 1 hour or longer, 2 hours or longer, 4 hours or longer, 24 hours or less, 12 hours or less, 8 hours or less, 6 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, or 45 minutes or less. In all aspects, the initial time period can be from greater than or equal to 10 minutes to less than or equal to 24 hours, from greater than or equal to 15 minutes to less than or equal to 12 hours, from greater than or equal to 30 minutes to less than or equal to 8 hours, from greater than or equal to 45 minutes to less than or equal to 6 hours, from greater than or equal to 1 hour to less than or equal to 4 hours, from greater than or equal to 1 hour to less than or equal to 2 hours, or any range or subrange thereof. Heating the glass article in step 405 can reduce the thermal shock to the glass article, thereby increasing the yield of the method and / or increasing the uniformity of the resulting compressive stress zone from steps 407 and / or 409. In all respects, the glass article heated in step 405 can be chemically strengthened immediately in step 407 without allowing it to cool for longer than the time necessary for transferring the glass article between steps.
[0104] Following steps 401, 403, or 405, the method may proceed to step 407, which includes at least contacting the existing first primary surface 603 of the glass articles 611 and / or 911 with a molten salt solution 703 maintained at a first temperature for a first time period to form a compressive stress zone (in the resulting chemically strengthened glass article), such as Figure 7As shown. In various aspects, the composition of molten salt solution 703 can be within one or more corresponding compositional ranges discussed above with respect to mixture 503 and / or molten salt solution 703 or 803 in step 403 (e.g., a mixture of alkali metal acetate and alkali metal carbonate). The properties of the initial compressive stress zone (e.g., maximum compressive stress, compression depth, layer depth) can be within one or more corresponding ranges discussed above. In various aspects, as Figure 7 As shown, molten salt solution 703 may be contained in molten salt bath 701, and then contacting at least the existing first main surface 603 with molten salt solution 703 may include immersing glass articles 611 and / or 911 in molten salt solution 703, for example, both the existing first main surface 603 and the existing second main surface 605 are in contact with molten salt solution 703, but in other respects only a portion of the foldable substrate may be in contact with molten salt solution. When a first cation within the depth of the surface of glass articles 611 and / or 911 exchanges with a second cation in molten salt solution 703 having a radius greater than that of the first cation, glass articles 611 and / or 911 can be chemically strengthened by ion exchange. For example, lithium cations within the said depth of the surface of glass articles 611 and / or 911 may exchange with sodium or potassium cations in molten salt solution 703. Similarly, sodium cations within the stated depth of the surface of glass articles 611 and / or 911 can exchange with potassium cations in the molten salt solution 703, thereby creating compressive stress within the glass articles 611 and / or 911. Therefore, since the radius of lithium cations is smaller than that of the exchanged sodium or potassium cations in the molten salt solution 703, the surface of glass articles 611 and / or 911 is compressed and thus chemically strengthened through the ion exchange process. In various aspects, the temperature of the heat-treated glass substrate can be maintained at a temperature greater than or equal to 200°C between steps 405 and 407. In various aspects, chemical strengthening of the foldable substrate (e.g., the heat-treated foldable substrate at the beginning of step 407) can begin immediately after the heat treatment in step 405. Avoiding large temperature fluctuations between steps 405 and 407 can reduce thermal shock (and potential damage) to the heat-treated foldable substrate.
[0105] In all aspects, the first time period during which the glass article 611 (e.g., the existing first main surface 603 and / or the existing second main surface 605) contacts the molten salt solution 703 can be 5 minutes or longer, 10 minutes or longer, 15 minutes or longer, 20 minutes or longer, 30 minutes or longer, 45 minutes or longer, 1 hour or longer, 2 hours or longer, 4 hours or longer, 8 hours or longer, 12 hours or longer, 16 hours or longer, or 20 hours or longer. 24 hours or longer, 30 hours or longer, 36 hours or longer, 48 hours or longer, 96 hours or less, 72 hours or less, 60 hours or less, 48 hours or less, 36 hours or less, 30 hours or less, 24 hours or less, 20 hours or less, 16 hours or less, 12 hours or less, 8 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 45 minutes or less, or 30 minutes or less. In all aspects, the first time period in which the glass article 611 (e.g., the existing first main surface 603 and / or the existing second main surface 605) contacts the molten salt solution 703 can be greater than or equal to 5 minutes and less than or equal to 96 hours, from greater than or equal to 10 minutes and less than or equal to 72 hours, from greater than or equal to 15 minutes and less than or equal to 60 hours, from greater than or equal to 20 minutes and less than or equal to 48 hours, from greater than or equal to 30 minutes and less than or equal to 36 hours, from greater than or equal to 45 minutes and less than or equal to 30 hours, from greater than or equal to 1 hour and less than or equal to 24 hours, from greater than or equal to 2 hours and less than or equal to 20 hours, from greater than or equal to 4 hours and less than or equal to 16 hours, from greater than or equal to 8 hours and less than or equal to 12 hours, or any range or subrange thereof. In all aspects, the first time period can be greater than or equal to 8 hours to obtain sufficient compressive stress and / or depth of compression, particularly when the first temperature is relatively low (e.g., from greater than or equal to 295°C to 345°C). For example, the first time period can be from 8 hours or more to 96 hours or less, from 12 hours or more to 72 hours or less, from 16 hours or more to 60 hours or less, from 20 hours or more to 48 hours or less, from 24 hours or more to 36 hours or less, from 30 hours or more to 36 hours or less, or any range or subrange thereof. In a preferred aspect, the first time period can be from 5 minutes or more to 96 hours or less, from 1 hour or more to 48 hours or less, from 8 hours or more to 36 hours or less, or any range or subrange thereof.
[0106] In various aspects, when the glass article includes lithium, in step 407, the chemically strengthened glass article 611 and / or 911 may include ion exchange between lithium in the glass article and sodium and / or potassium in the molten salt solution. In a further aspect, in step 407, the lithium ions exchanged from the glass article may react with carbonate anions of an alkali metal carbonate to form lithium carbonate. In an even further aspect, the lithium carbonate formed during step 405 may be a lithium carbonate precipitate deposited at the bottom of the molten salt bath 701 containing the molten salt solution 703.
[0107] Alternatively, in step 409, a molten salt solution 803 containing a mixture of alkali metal acetates and alkali metal carbonates (see...) Figure 8 When further chemically strengthening glass products in molten salt solution 703 (see...) Figure 7 The alkali metal may include alkali metal nitrates, alkali metal phosphates, alkali metal sulfates, alkali metal carbonates, or combinations thereof. In a further aspect, the alkali metal in the molten salt solution 703 may include sodium and optionally potassium. Additionally, in a further aspect, the temperature of the molten salt solution 703 may be any range or subrange from 330°C to 530°C, from 350°C to 500°C, from 360°C to 470°C, from 370°C to 450°C, from 380°C to 430°C, from 390°C to 400°C, or between. In a further aspect, the first time period may be within one or more corresponding ranges discussed in step 407 in the preceding paragraphs.
[0108] Following step 407, in various respects, the method may proceed to step 409, including further chemically strengthening the glass articles 611 and / or 911 by contacting at least a portion of the glass articles 611 and / or 911 with a second molten salt solution 803 maintained at a second temperature for a second time period, as... Figure 8As shown. In various aspects, as illustrated, step 409 may include immersing glass articles 611 and / or 911 in a second molten salt solution 803 contained in a second bath 801. In various aspects, the second molten salt solution 803 may include a mixture of alkali metal acetates and alkali metal carbonates, said mixture being within one or more corresponding ranges discussed above with reference to step 403 for mixture 503 and / or molten salt solution 703. In a further aspect, the second molten salt solution may include a mixture of potassium acetate and potassium carbonate. In a further aspect, the second molten salt solution 803 may consist of alkali metal acetates and alkali metal carbonates. In a further aspect, the second temperature may be within one or more ranges discussed above with reference to step 407 (e.g., from 295°C to 475°C, from 310°C to 400°C, from 320°C to 345°C). Alternatively, in various aspects, the second molten salt solution 803 may include alkali metal nitrates (e.g., potassium nitrate) and / or other alkali metal salts. In a further aspect, the second temperature may be within one or more of the ranges discussed in the preceding paragraph (e.g., from 330°C to 530°C, from 350°C to 450°C, from 370°C to 400°C).
[0109] In all respects, the second time period can be 1 minute or longer, 5 minutes or longer, 10 minutes or longer, 15 minutes or longer, 20 minutes or longer, 30 minutes or longer, 45 minutes or longer, 1 hour or longer, 2 hours or longer, 4 hours or longer, 8 hours or longer, 12 hours or longer, 16 hours or longer, 24 hours or less, 20 hours or less, 16 hours or less, 12 hours or less, 8 hours or less, 4 hours or less, 2 hours or less, 1 hour or less, 45 minutes or less, 30 minutes or less, or 20 minutes or less. In all respects, the second time period in which the glass article 611 (e.g., the existing first main surface 603 and / or the existing second main surface 605) is in contact with the molten salt solution 703 can be greater than or equal to 1 minute and less than or equal to 24 hours, from greater than or equal to 5 minutes and less than or equal to 20 hours, from greater than or equal to 10 minutes and less than or equal to 16 hours, from greater than or equal to 15 minutes and less than or equal to 12 hours, from greater than or equal to 20 minutes and less than or equal to 8 hours, from greater than or equal to 30 minutes and less than or equal to 4 hours, from greater than or equal to 45 minutes and less than or equal to 2 hours, from greater than or equal to 1 hour and less than or equal to 2 hours, or any range or subrange thereof.
[0110] In various aspects, after step 407 or 409, the method may proceed to step 411, including further processing the chemically strengthened glass article 901 and / or assembling a consumer electronic device 100 and / or 301 containing the chemically strengthened glass article 901. In various aspects, further processing of the chemically strengthened glass article 901 may include rinsing the chemically strengthened glass article 901 (e.g., in deionized water or an alkaline detergent solution) and / or etching the chemically strengthened glass article 901 to remove material smaller than 5 µm from each surface, which may increase the mechanical strength of the chemically strengthened glass article 901. An exemplary aspect of the alkaline detergent solution includes SemiClean KG (Yokohama Oils & FatsIndustry Co.).
[0111] Following steps 407, 409, and / or 411, the method may be completed at step 413. At the end of steps 407, 409, 411, and / or 413, the chemically strengthened glass articles 611 and / or 911 may correspond to those described above and are... Figure 9 The chemically strengthened glass article 901 is shown. In various aspects, the method can be carried out according to the steps described above, for example, sequentially through steps 401, 403, 405, 407, 409, 411, and 413. In various aspects, the method can proceed from step 401 to step 405 according to arrow 402, for example, if a molten salt solution has been prepared at the end of step 401, or if the molten salt solution is subsequently formed in step 403 by heating a mixture of alkali metal acetate and alkali metal carbonate according to arrow 404 from step 405 to step 403. In various aspects, if the glass article is not heated before chemical strengthening in step 407, or if the method proceeds from step 405 to step 403 according to arrow 404, then the method can proceed from step 403 to step 407 according to arrow 406. In various aspects, if a molten salt solution has been prepared by the end of step 401 and the glass article is not heated before chemical strengthening in step 407, then the method can proceed from step 401 to step 407 according to arrow 414. In all aspects, if no further chemically strengthened glass articles are produced after step 407, the method may proceed from step 407 to step 411 according to arrow 408. In all aspects, if the method is completed at the end of step 407, the method may proceed from step 407 to step 413 according to arrow 410. In all aspects, if the method is completed at the end of step 409, the method may proceed from step 409 to step 413 according to arrow 412. Any of the above options may be combined to produce chemically strengthened glass articles according to aspects of this disclosure.
[0112] In various aspects, the methods according to this disclosure can consist of the steps described above. For example, as referenced above... Figure 4 The foldable substrate may be left unprocessed between one or more (or even all) steps described in the flowchart. Throughout this disclosure, the phrase "no further processing" or "not subject to further processing" excludes processing of the first primary surface, except for the stated contact with a solution and rinsing with water (e.g., purified water, filtered water, deionized water, distilled water). Exemplary aspects of processing that may be excluded under "no further processing" or "not subject to further processing" include treatments using additional acidic solutions, alkaline solutions, fluorinated solutions, cleaning agents, and mechanical polishing of the foldable substrate.
[0113] Example
[0114] The following references will be used Figure 10-14 The examples further illustrate various aspects. The glass substrates used in the examples here have composition C1 (nominally expressed in mole % as follows: 67.6 SiO2; 12.7 Al2O3; 3.7 B2O3; 0 Li2O, 13.6 Na2O, 0 K2O, 2.34 MgO, and 0.1 SnO2) or composition C2 (nominally expressed in mole % as follows: 64.5 SiO2; 15.9 Al2O3; 0 B2O3; 6.3 Li2O; 11.0 Na2O; 0 K2O; 1.2 ZnO; and 1.1 P2O5) with a thickness of 1.1 mm, unless otherwise specified. Compositions C1-C2 are all alkali aluminosilicate glasses, and composition C2 is a lithium-containing aluminosilicate glass. All samples were heated at 250°C for 30 minutes prior to chemical strengthening.
[0115] molten salt solution of potassium acetate
[0116] First, a molten salt solution is formed by heating potassium acetate at 340°C. Figure 10 The diagram schematically illustrates that, according to aspects of this disclosure, for a molten salt solution or its components, the infrared transmittance (T%) on the vertical axes 1003, 1023, and 1043 (i.e., the y-axis) varies with the horizontal axis 1001 (i.e., the x-axis) in centimeters. -1 (cm) -1 The value varies with wavenumber (WN) in units of 1005. Curve 1005 corresponds to a molten salt solution obtained less than 2 hours after potassium acetate has completely melted. The broad absorption band 1006 is associated with hydroxyl groups, which can originate from ambient water or acetate anions. Absorption band 1007 is associated with CH bonds. Absorption bands 1008, 1009, 1010, 1011, 1012, and 1013 are located at 1560.9 cm⁻¹. -1 1398.0 cm-1 1334.7 cm -1 1051.9 cm -1 1007.3 cm -1 and 914.5 cm -1 It has the maximum absorption at the wavenumber.
[0117] A molten salt solution was then formed by heating potassium acetate at 340°C and maintaining that temperature for 24 hours. During this 24-hour period, the molten salt solution changed from clear and transparent to dark and opaque. Furthermore, black solid residues were observed on the surface of the molten salt solution. Figure 10 In the diagram, curve 1025 corresponds to the spectrum of the black solid residue, and curve 1045 corresponds to the molten salt solution after heating at 340 °C for 24 hours. For curve 1025, the broad absorption band 1026 is similar to the hydroxyl absorption band seen on curve 1005, but the absorption band 1007 associated with the CH bond in curve 1005 disappears. However, curve 1045 has a broad absorption band 1046, containing absorption bands similar to those associated with hydroxyl and CH bonds in curve 1005. This indicates that the alkyl portion of the acetate anion (in potassium acetate) has been transformed in the residue (curve 1025), but some of the acetate remains in the entire molten salt solution even after prolonged heating (curve 1045). Absorption bands 1028 and 1029 in curve 1025 correspond to absorption bands 1048 and 1049 in curve 1045 and absorption bands 1008 and 1009 in curve 1005. However, curve 1025 differs from curves 1005 and 1045 in the presence of absorption band 1027 (compared to the small absorption band 1047 in curve 1045 and the unlabeled absorption band in curve 1005). Furthermore, absorption band 1030 in curve 1025 is wider than absorption bands 1010 or 1050 seen in curves 1005 or 1045, respectively. Additionally, arrow 1036 points to an absorption band in curve 1025 that is missing relative to curves 1005 and 1045. For absorption bands 1031, 1032, and 1034 in region 1037, they are shifted to higher wavenumbers by approximately 25 cm relative to their corresponding absorption bands 1011-1013 in curve 1005. -1 up to 30 cm -1Other differences include a shallower absorption band 1034 than absorption band 1013. Furthermore, absorption bands 1033 and 1035 appear in curve 1025 relative to curve 1005. In summary, these changes indicate that the acetate anion in the residue has been transformed, but some carbon bonds remain to other components (heavier than hydrogen). Turning to curve 1045, the small absorption band 1056 in region 1057 is new relative to curves 1005 and 1025. Absorption band 1051 is similar to absorption band 1031 (relative to absorption band 1011) shifted to a higher wavenumber, but absorption bands 1052 and 1053 appear in positions similar to absorption bands 1012 and 1013. Furthermore, absorption band 1054 in region 1059 appears to correspond to absorption band 1035, while absorption band 1055 in region 1061 is completely new relative to curves 1005 and 1025. In summary, the retained absorption band in curve 1045 relative to curve 1005 indicates that a considerable portion of the potassium acetate remains, but the new absorption band in curve 1045 relative to curve 1005 (mostly the same as the absorption band seen in curve 1025) indicates that some of the acetate anions have undergone some reaction (e.g., decomposition), which may have led to the observed residue.
[0118] To further investigate the changes of potassium acetate molten salt solution over time, Figure 10 The samples underwent thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The TGA and DSC results are shown in [link to table]. Figure 11-13 .exist Figure 11-13 In the diagram, the weight (WT%) loss (from TGA) on the left vertical axes 1103, 1203, and / or 1303 and the heat flux (mW / mg) (from DSC) on the right vertical axes 1113, 1213, and / or 1313, specified by plus or minus signs indicated by arrows 1111, 1211, and / or 1311, vary with the temperature (T) on the horizontal axes 1101, 1201, and / or 1301 (i.e., the x-axis) for one or more components of the molten salt solution. Curves 1105, 1205, and 1305 correspond to the weight % of the sample (from TGA), while curves 1115, 1215, and 1315 correspond to the heat flux of the sample (from DSC). Curves 1105 and 1115 correspond to the molten salt solution; curves 1205 and 1215 correspond to the black solid residue; and curves 1305 and 1315 correspond to the molten salt solution after heating at 340°C for 24 hours. For TGA and DSC, the temperature increases at a rate of 5°C / min within the plotted temperature range.
[0119] for Figure 11Curve 1115 exhibits an endothermic shift 1117 near 300 °C, corresponding to the melting point of potassium acetate. A broad exothermic shift 1119 is observed from approximately 325 °C to approximately 440 °C, with a maximum exothermic effect near 425 °C, likely due to the reaction of potassium acetate (e.g., partial decomposition). Subsequently, a sharp exothermic spike 1121 is seen near 480 °C, possibly associated with thermal decomposition. Observing curve 1105, no change is observed near 300 °C, confirming that the endothermic shift 1117 seen in curve 1115 is caused by the melting of potassium acetate. Region 1107 of curve 1105 shows a mass loss starting from approximately 350 °C to 370 °C and accelerating until approximately 425 °C, corresponding to the broad exothermic shift 1119 seen in curve 1115. This indicates that the reaction (broad exothermic shift 1119) causes some mass loss (region 1107), potentially leading to the release of gases or other small volatile compounds. Returning to curve 1105, region 1109 shows an accelerated weight loss from approximately 450 °C to approximately 480 °C, corresponding to a sharp exothermic spike 1121 (seen in curve 1115), indicating further reaction and / or thermal decomposition of at least some potassium acetate. However, at 500 °C, at least 70 wt% of the initial molten salt solution remains, suggesting that not all potassium acetate has decomposed. Instead, we assume a local equilibrium has been reached between potassium acetate and the decomposition products, at least on the timescale of the temperature ramp based on the flatness of curve 1105 near 500 °C. However, if thermal decomposition involves the release of gases or other volatile compounds, further decomposition is possible (as further demonstrated in this section), suggesting that pure potassium acetate is not thermally stable.
[0120] for Figure 12 Curve 1215 does not exhibit an endothermic shift, indicating that the residue has no melting point within this range. Instead, a sharp exothermic peak 1217 is observed between 350°C and approximately 375°C before the heat flux approaches zero. Meanwhile, curve 1205 is flat until region 1207, where more than 80% by weight of the sample volatilizes, except for some low-temperature (below 100°C) weight loss possibly due to absorbed water or carbon dioxide. This suggests that the residue may undergo thermal decomposition above 350°C.
[0121] for Figure 13 Curve 1315 exhibits an endothermic shift 1317 corresponding to the melting of the material in the molten salt solution, as shown by the endothermic shift 1117 in curve 1115. Compared to curve 1115, Figure 11The broad exothermic shift 1119, separating from the acute exothermic peak 1121, is replaced by a narrower, higher-temperature exothermic shift 1319 leading to the acute exothermic peak 1321. This indicates that most of the reaction associated with the broad exothermic shift 1119 must have occurred during the 24 hours the molten salt solution was held at 340°C (although the broad exothermic shift 1119 is not significant at 340°C). Indeed, a portion of the molten salt solution exhibits higher temperatures and / or further thermal decomposition in the narrower exothermic shift 1319 and the acute exothermic peak 1321 in curve 1315. Turning to curve 1305, a significant weight loss is seen only in region 1307. Compared to curve 1105, the weight loss in region 1107 appears to have disappeared, and region 1109 roughly corresponds to region 1307. This further confirms... Figure 11 The weight loss in region 1107 associated with the wide exothermic shift 1119 is in Figure 13 The absence of an explanation in the text could be due to those reactions already occurring, potentially leading to... Figure 12 The formation of residues analyzed in the middle.
[0122] As discussed above and in Figure 11-12 As observed, the broad exothermic shift 1119 in curve 1115 appears to lead to the formation of a residue that undergoes an exothermic reaction, resulting in a significant associated weight loss in the abrupt exothermic peak 1217 and region 1207, which decreases most significantly between 350°C and 375°C. Therefore, providing the molten salt solution with a temperature less than or equal to 350°C can avoid Figure 11-13 The observed thermal degradation (but not all, as can be seen from the formation of residues) can increase the stability and / or lifespan of the molten salt solution at the corresponding temperature. Based on the infrared, TGA, and DSC analyses discussed above and comparisons with literature values, we believe that a portion of the potassium acetate thermally decomposes into potassium carbonate, which is associated with the formation of residues.
[0123] A molten salt solution of potassium acetate and a mixture of potassium carbonate.
[0124] Next, a molten salt solution S1 was formed by heating 100 wt% potassium acetate. A molten salt solution S2 was formed by heating a mixture of 91 wt% potassium acetate and 9 wt% potassium carbonate. Both molten salt solutions S1 and S2 were heated at 340°C for 10 days, and the weight loss (wt%) was measured to characterize the long-term thermal stability of the molten salt solutions. The weight loss of molten salt solution S1 was 6.16 wt%, while that of the molten salt solution S2 was 5.05 wt%. This demonstrates that starting with a mixture of potassium acetate and potassium carbonate increases thermal stability compared to pure potassium acetate. Without being bound by strict theoretical requirements, we believe that the addition of potassium carbonate shifts the thermodynamic equilibrium towards potassium acetate, thereby reducing the thermal decomposition of potassium acetate (compared to potassium acetate alone). Furthermore, since this experiment... Figure 11-13Regarding the higher weight loss observed, we believe that if the storage time is longer (even below 350°C), the thermal decomposition of the molten salt solution S1 will continue to increase. Furthermore, without adhering strictly to theory, we believe that adding more than 5% by weight (e.g., from 5% to 20% by weight, or from 8% to 15% by weight) of carbonate (potassium carbonate in this case) may exceed the amount of carbonate formed from a pure (potassium) acetate molten salt solution; thus, the composition formed according to this disclosure from a heated mixture of alkali metal acetate and alkali metal carbonate may not be formed from the thermal decomposition of a pure alkali metal acetate molten salt solution. Moreover, starting with a mixture of alkali metal acetate and alkali metal carbonate can reduce the amount of residue formed, as the mixture is considered closer to equilibrium than a pure alkali metal acetate molten salt solution.
[0125] Chemically enhanced samples in a single molten salt solution
[0126] Third, samples of composition C1 were chemically fortified in a potassium acetate molten salt solution maintained at 340°C for 24 hours. Six batches of samples of composition C1 were sequentially chemically fortified in this potassium acetate molten salt solution after heating the molten salt solution at 340°C for 4 hours prior to the first batch to assess the consistency (or degradation) of the compressive stress layer formed over time, which could be used to evaluate the usable lifespan of the molten salt solution. The properties of these samples are shown in Table 1. In Table 1, DOL corresponds to the layer depth of potassium ions from ion exchange with the potassium acetate molten salt solution in the sample; weight gain refers to the change (i.e., increase) in sample weight after chemical fortification compared to before chemical fortification. Furthermore, the pH of the molten salt solution was measured after each batch of samples.
[0127] Table 1: Properties of chemically fortified composition C1 in potassium acetate molten salt solution at 340°C for 24 hours
[0128] batch Compressive stress (MPa) DOL (µm) Weight gain (%) pH of molten salt solution 1 966 28.7 0.119 10.00 2 954 28.7 0.125 10.50 3 940 28.7 0.115 10.95 4 942 28.2 0.123 11.05 5 948 28.7 0.126 11.16 6 946 28.8 0.130 11.13
[0129] As shown in Table 1, the compressive stress in consecutive batches of samples was fairly consistent, differing by an average of approximately 25 MPa or less across the batch series. Furthermore, the compressive stresses of the last 3 or 4 batches were essentially the same. Similarly, the DOL (Density Oxide) was essentially the same across all batches (between 28 µm and 29 µm). The weight gain gradually increased with increasing batch number but did not impair the properties of the resulting glass articles. The pH values for pure potassium acetate (8.08) and pure potassium carbonate (11.94) were reported above. Here, the pH values of these batches remained between 10.0 and 11.2, indicating the presence of significant amounts of potassium carbonate (e.g., from 5 wt% to 20 wt%, from 8 wt% to 15 wt%) in these batches (e.g., over approximately one week).
[0130] Chemically enhanced samples in various molten salt solutions
[0131] Fourth, samples of chemically strengthened composition C2 in acetate molten salt solutions: first molten salt solution S3, followed by second molten salt solution S4. First molten salt solution S3 contains 25% by weight of sodium salt and 75% by weight of potassium salt, while second molten salt solution S4 contains 100% by weight of potassium salt. Both molten salt solutions S3 and S4 are maintained at 340°C. As mentioned above, composition C2 is lithium-containing aluminosilicate glass. Table 2 presents the duration of the chemical strengthening treatments and the properties after each treatment. In Table 2, adding "1" indicates that the condition or property refers to the first chemical strengthening treatment, while adding "2" indicates that the condition or property refers to the second chemical strengthening treatment. For example, t1 refers to the duration of the first chemical strengthening treatment in hours (h), while t2 refers to the duration of the second chemical strengthening treatment (also in hours). "CS" refers to the maximum compressive stress measured in the compressive stress zone at the end of the corresponding chemical strengthening treatment, and "WG" refers to the weight gain of the sample at the end of the chemical strengthening treatment (relative to before the treatment). Therefore, WG2 refers only to the increase in sample weight after the second chemical strengthening treatment, while CS2 and DOL2 refer to the compressive stress and DOL measured in the resulting article, respectively (without needing to be compared with the earlier stages).
[0132] Table 2: Conditions and properties of chemically fortified composition C2
[0133] sample t1(h) CS1 (MPa) DOL1 (µm) WG1 (%) t2(h) CS2 (MPa) DOL2 (µm) WG2 (%) X1 96 858 42.2 0.963 5 969 42.0 0.031 X2 96 855 42.2 0.933 15 974 44.0 0.070 X3 96 854 42.5 0.972 24 979 44.0 0.089 X4 24 924 19.7 0.505 5 1129 21.4 0.077
[0134] As shown in Table 2, the first chemical strengthening treatment of 96 hours (samples X1-X3) produced a compressive stress of approximately 855 MPa and a layer depth of approximately 42.2 µm, with a weight gain of less than 1%. Compared to the 96-hour treatment, the first chemical strengthening treatment of 24 hours (sample X4) produced a greater compressive stress (924 MPa), but a shallower DOL (197 µm), and a weight gain of approximately half that of the 96-hour treatment. For the second chemical strengthening treatment, the duration increased from 5 hours (sample X1) to 24 hours (sample X3). At the end of the second chemical strengthening treatment for samples X1-X3, the resulting compressive stress was approximately 975 MPa, the resulting DOL was approximately 44 µm, and the additional weight gain was less than 0.1%. Within these samples (X1-X3), the compressive stress increased by approximately 5 MPa / 12 hours, the weight gain increased with increasing duration, and the DOL increased from sample X1 to sample X2, but remained the same for samples X2 and X3. Both samples X1 and X4 underwent a second chemical enhancement treatment for 5 hours, but the first chemical enhancement treatment for sample X1 was 96 hours, while that for sample X4 was 24 hours. As with the first chemical enhancement step, after the second chemical enhancement step, sample X4 exhibited a higher CS (1129 MPa > 969 MPa) but a lower DOL (21.4 µm < 42.0 µm) compared to sample X1. However, due to the smaller ion exchange range (e.g., shallower DOL) in the first chemical enhancement treatment compared to sample X1, sample X4 had a larger WG2 (0.077% > 0.031%) (but a smaller overall weight gain = WG1 + WG2).
[0135] Comparison of properties between products fortified with acetate and nitrate
[0136] Fifth, the failure strength (measured in ring-to-ring testing) of a sample of composition C1 chemically strengthened in potassium acetate molten salt solution (sample Y1) was compared with the failure strength of another sample of composition C1 chemically strengthened in potassium nitrate molten salt solution (sample Y2). Table 3 presents the properties of samples Y1 and Y2; Figure 15 The stress distribution is shown in the figure; the reported B10 failure strength is taken from... Figure 14 The results are presented in the table. The conditions for each chemical strengthening treatment were to maintain the corresponding molten salt bath at 440°C for 4 hours. This was chosen to achieve similar compressive stress (4 MPa difference) and DOC (see [reference]). Figure 15 ) and DOL (1.3µm) values.
[0137] Table 3: Properties of samples Y1 and Y2
[0138] sample Compressive stress (MPa) DOL (µm) Weight gain (%) B10 failure strength (MPa) Y1 926 30.9 0.121 1382.3 Y2 942 29.6 0.117 1373.0
[0139] Figure 15 The stress distribution is schematically illustrated, where the compressive stress (CS) on the vertical axis 1503 (i.e., the y-axis) varies with the depth (d) on the horizontal axis 1501 (i.e., the x-axis) from the surface of the chemically strengthened glass article in micrometers (µm). Curve 1505 corresponds to the stress distribution of sample Y1, and curve 1507 corresponds to the stress distribution of sample Y2. Figure 15 Only the first 30 µm of the stress distribution is shown. (Example) Figure 15 As shown in Table 2, the stress distribution is extremely similar. For example, the (maximum) compressive stress is within approximately 2%, and the DOC and DOL are each within approximately 5%. More specifically, compared to sample Y2, sample Y1 has a lower (maximum) compressive stress, but higher DOC and DOL. Furthermore, as... Figure 15 As shown, the deeper part of the compressive stress distribution of sample Y1 (curve 1505) is slightly higher than that of sample Y2 (curve 1507).
[0140] Figure 14 The Weibull distribution of chemically strengthened glass articles is schematically illustrated by varying the failure percentile (F%) on the vertical axis 1403 (i.e., the y-axis) with the failure strength (S) in megapascals (MPa) during ring-to-ring testing on the horizontal axis 1401 (i.e., the x-axis). Figure 14 In the diagram, curves 1407 and 1417 correspond to distributions fitted to data 1405 and 1415, respectively. Furthermore, confidence intervals 1409a-1409b correspond to the distribution centered on curve 1407, and confidence intervals 1419a-1419b correspond to the distribution centered on curve 1417. The diagram shows the B10 intensities 1408 and 1418 corresponding to curves 1407 and 1417 based on data 1405 and 1415, respectively, representing the failure intensity (S) at the 10th percentile. Figure 14 In comparison, the B10 strength 1408 of Example AA is 1373 MPa, and the B10 strength 1418 of Example 1 is 1382 MPa.
[0141] The above observations can be combined to provide a method for chemically strengthening glass articles. A mixture of alkali metal acetates and alkali metal carbonates can be used to chemically strengthen glass articles. Providing a molten salt solution as a mixture of alkali metal acetates and alkali metal carbonates simplifies the disposal and / or disposal costs associated with the mixture because it is non-explosive and / or more environmentally friendly compared to alkali metal nitrates. Furthermore, alkali metal acetates and alkali metal carbonates can be cheaper than alkali metal nitrates. Additionally, a molten salt solution of a mixture of alkali metal acetates and alkali metal carbonates can reduce greenhouse gas emissions compared to a comparative molten salt solution consisting only of alkali metal nitrates, because the molten salt solution of the mixture can be formed at a lower temperature than the comparative molten salt solution, and the molten salt solution of the mixture does not produce the same level of nitrogen oxides (NOx) or other greenhouse gases as the comparative molten salt solution during use in chemically strengthening glass articles. Furthermore, as illustrated in the examples herein, the molten salt solution of the mixture can limit the reduction of compressive stress formed in the continuous chemical strengthening process of continuous glass articles, compared to a molten salt solution formed solely by alkali metal nitrates, for example, by the reaction of carbonates in the mixture with lithium ions exchanged from the glass articles into the molten salt solution.
[0142] Without being bound by theory, we believe that adding alkali metal carbonates will shift the thermodynamic equilibrium towards potassium acetate, thereby reducing the thermal decomposition of alkali metal acetates (compared to potassium acetate alone). Furthermore, without being bound by theory, we believe that adding more than 5% by weight (e.g., from 5% to 20% by weight, or from 8% to 15% by weight) of carbonate may exceed the amount of carbonate formed from a molten alkali metal acetate solution. Thus, the composition obtained according to this disclosure by heating a mixture of alkali metal acetates and alkali metal carbonates may not be formed from the thermal decomposition of a molten alkali metal acetate solution. Moreover, starting with a mixture of alkali metal acetates and alkali metal carbonates can reduce the amount of residue formed, because the mixture is considered closer to equilibrium than a molten alkali metal acetate solution.
[0143] Providing the molten salt solution with temperatures below or equal to 475°C, 400°C, and / or 345°C can reduce the amount of thermal decomposition of alkali metal acetates, which can increase the service life of the molten salt solution. Providing a initial temperature below or equal to 350°C can prevent... Figure 11-13 Most of the thermal degradation observed here can further increase the stability and / or lifespan of the molten salt solution at the corresponding temperature. As the examples here demonstrate, providing a mixture of alkali metal acetates and alkali metal carbonates as raw materials and / or in the molten salt solution increases the thermal stability of the corresponding molten salt solution.
[0144] As used in this article, directional terms such as up, down, right, left, front, back, top, and bottom are for reference only in the illustrations and are not intended to imply absolute orientation.
[0145] It will be understood that the various disclosed aspects may relate to features, elements, or steps described in conjunction with those aspects. It should also be understood that although a feature, element, or step is described with respect to one aspect, it may be interchanged or combined with alternative aspects in various combinations or arrangements not illustrated.
[0146] It should also be understood that, as used herein, the terms “the,” “a,” or “an” mean “at least one,” and should not be limited to “only one” unless explicitly indicated otherwise. Thus, by way of example, unless the context explicitly indicates otherwise, references to “component” include aspects having two or more such components. Similarly, “multiple” is intended to mean “more than one.”
[0147] As used herein, the terms “substantial,” “substantially,” and their variations are intended to indicate that the described feature is equal to or approximately equal to a value or description. For example, a “substantially flat” surface is intended to mean a flat or approximately flat surface. Furthermore, as defined above, “substantially similar” is intended to mean that two values are equal or approximately equal. In all respects, “substantially similar” can mean values that differ from each other by approximately 10%, such as values that differ from each other by approximately 5%, or values that differ from each other by approximately 2%.
[0148] Unless otherwise expressly stated, it is not intended to interpret any method described herein as requiring its steps to be performed in a particular order. Therefore, no particular order is intended to be inferred where the method claims do not actually enumerate the order in which the steps are performed, or where the claims or description do not specifically specify that the steps should be limited to a particular order.
[0149] The transitional phrase "comprising" can be used to disclose various features, elements, or steps of a particular aspect; however, it should be understood that it implies alternative aspects that include those aspects that can be described using the transitional phrases "consisting of" or "substantially consisting of." Thus, for example, the implicit alternative aspect of a device comprising A+B+C includes both the aspect of the device being composed of A+B+C and the aspect of the device being substantially composed of A+B+C. As used herein, the terms "comprising" and "including," and variations thereof, should be understood as synonyms and open-ended unless otherwise specified.
[0150] The foregoing aspects and features thereof are exemplary and may be provided individually or in any combination with any one or more features of other aspects provided herein without departing from the scope of this disclosure.
[0151] It will be apparent to those skilled in the art that various modifications and changes can be made to this disclosure without departing from its spirit and scope. Therefore, it is intended that this disclosure cover modifications and variations to the aspects herein, provided that they fall within the scope of the appended claims and their equivalents.
Claims
1. A method for producing a chemically strengthened glass product, the method comprising: The glass article is contacted with a molten salt solution comprising alkali metal acetates and alkali metal carbonates, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C to less than or equal to 475°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article including a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa to less than or equal to 1500 MPa. Prior to the contact, the glass article comprises lithium, and the contact is achieved by chemically strengthening the glass article through ion exchange between the lithium in the glass article and potassium in the molten salt solution.
2. The method according to claim 1, further comprising heating the mixture of the alkali metal acetate and the alkali metal carbonate to the first temperature prior to the contact, wherein the heating melts the mixture to form the molten salt solution.
3. A method for producing chemically strengthened glass articles, the method comprising: A mixture of alkali metal acetate and alkali metal carbonate is heated to a first temperature, wherein the heating melts the mixture to form a molten salt solution; as well as The glass article is brought into contact with a molten salt solution comprising the alkali metal acetate and the alkali metal carbonate, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C to less than or equal to 475°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article comprising a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa to less than or equal to 1500 MPa.
4. The method according to any one of claims 2 to 3, wherein the mixture of the alkali metal acetate and the alkali metal carbonate comprises, based on 100% by weight of the mixture: The alkali metal acetates range from 80% or more by weight to 95% or less by weight; as well as The alkali metal carbonates range from 5% or more by weight to 20% or less by weight.
5. The method according to any one of claims 1 to 4, wherein the molten salt solution exhibits a weight loss of less than or equal to 5.5% by weight when maintained at the first temperature for 10 days without the contact.
6. A method for producing a chemically strengthened glass product, the method comprising: The glass article is contacted with a molten salt solution comprising alkali metal acetates and alkali metal carbonates, the molten salt solution being maintained at a first temperature of greater than or equal to 295°C and less than or equal to 345°C for a first time period to form a chemically strengthened glass article, the chemically strengthened glass article including a compressive stress zone having a maximum compressive stress of greater than or equal to 400 MPa and less than or equal to 1500 MPa. The molten salt solution exhibits a weight loss of less than or equal to 5.5% by weight when maintained at the first temperature for 10 days without the contact.
7. The method according to any one of claims 1 to 6, wherein the molten salt solution comprises, based on 100% by weight of the molten salt solution: The alkali metal acetates range from 80% or more by weight to 95% or less by weight; as well as The alkali metal carbonates range from 5% or more by weight to 20% or less by weight.
8. The method according to any one of claims 1 to 7, wherein the total amount of the alkali metal acetate and the alkali metal carbonate in the molten salt solution is equal to 100% by weight of the molten salt solution.
9. The method according to any one of claims 1 to 8, wherein the alkali metal acetate is potassium acetate and the alkali metal carbonate is potassium carbonate.
10. The method according to any one of claims 1 to 9, wherein the alkali metal acetate is sodium acetate and the alkali metal carbonate is sodium carbonate.
11. The method according to any one of claims 1 to 9, wherein the alkali metal acetate is a combination of sodium acetate and potassium acetate, and the alkali metal carbonate is a combination of sodium carbonate and potassium carbonate.
12. The method of claim 11, wherein the weight % ratio of potassium to sodium in the molten salt solution is from 66:33 to 99:
1.
13. The method according to any one of claims 1 to 12, wherein the pH of the sample of the molten salt solution is from greater than or equal to 10.0 to less than or equal to 11.
2.
14. The method according to any one of claims 1 to 13, wherein the first temperature is from greater than or equal to 310°C to less than or equal to 400°C.
15. The method of claim 14, wherein the first temperature is from greater than or equal to 320°C to less than or equal to 345°C.
16. The method according to any one of claims 1 to 15, wherein the first time period is from greater than or equal to 5 minutes to less than or equal to 96 hours.
17. The method according to any one of claims 1 to 16, wherein the contact comprises immersing the glass article in a molten salt bath containing the molten salt solution, and the contact forms a lithium carbonate precipitate deposited at the bottom of the molten salt bath.
18. The method according to any one of claims 1 to 17, wherein the maximum compressive stress is from greater than or equal to 800 MPa to less than or equal to 1200 MPa.
19. The method according to any one of claims 1 to 18, wherein the composition corresponding to the body of the glass article comprises, based on 100 mol% of the composition: From greater than or equal to 50 mol% to less than or equal to 80 mol% of SiO2; Al2O3 ranging from greater than or equal to 1 mol% to less than or equal to 30 mol%; From greater than or equal to 0 mol% to less than or equal to 10 mol% of B2O3; P2O5 from greater than or equal to 0 mol% to less than or equal to 15 mol%; From 2 mol% or more to 40 mol% or less, Li₂O; as well as RO ranges from greater than or equal to 0 mol% to less than or equal to 30 mol%, where RO is the total amount of MgO, CaO, SrO, BaO, and ZnO.
20. The method of claim 19, wherein the composition corresponding to the body of the glass article comprises: From 52 mol% or more to 70 mol% of SiO2; Al2O3 ranging from 5 mol% to 20 mol%; From 5 mol% to 25 mol% of Li₂O; B2O3 from greater than or equal to 0 mol% to less than or equal to 8 mol%; From greater than or equal to 0 mol% to less than or equal to 5 mol% of P2O5; and RO from greater than or equal to 1 mol% to less than or equal to 20 mol%.
21. The method according to any one of claims 19 to 20, wherein the composition corresponding to the body of the glass article further comprises from greater than or equal to 1.0 mol% to less than or equal to 12 mol% of Na2O.
22. The method according to any one of claims 1 to 21, wherein the glass article is unstrengthened prior to the contact.
23. The method according to any one of claims 1 to 22, the method further comprising contacting the chemically strengthened glass article with a second molten salt solution, the second molten salt solution being maintained at a second temperature from greater than or equal to 295°C to less than or equal to 475°C for a second time period from greater than or equal to 1 minute to less than or equal to 24 hours, wherein the second molten salt solution comprises potassium acetate and potassium carbonate, and the molten salt solution that contacted the glass article prior to the second molten salt solution comprises sodium acetate and sodium carbonate.
24. The method according to any one of claims 1 to 22, the method further comprising contacting the chemically strengthened glass article with a second molten salt solution, the second molten salt solution being maintained at a second temperature from greater than or equal to 330°C to less than or equal to 530°C for a second time period from greater than or equal to 1 minute to less than or equal to 24 hours, wherein the second molten salt solution comprises potassium nitrate, and the molten salt solution that contacted the glass article prior to the second molten salt solution comprises sodium acetate and sodium carbonate.
25. The method according to any one of claims 1 to 24, further comprising heating the glass article at an initial temperature of greater than or equal to 200°C to less than or equal to 300°C for a period of time from greater than or equal to 10 minutes to less than or equal to 24 hours prior to the contact, wherein the contact occurs immediately after the heating of the glass article.
26. The method according to any one of claims 1 to 25, wherein the chemically strengthened glass article has a B10 failure strength greater than or equal to 1380 MPa in a ring-to-ring test.
Citation Information
Patent Citations
Systems and methods for measuring a profile characteristic of a glass sample
US8854623B2